An existential support program for people with cancer: Development and qualitative evaluation. (June 2020) - Assing Hvidt, Elisabeth; Hvidt, Niels Christian; Graven, Vibeke; la Cour, Karen; Rottmann, Nina; Thomsen, Karsten Flemming; Lindqvist, Ole; Rasmussen, Annette; Skaarup, Helle; Roessler, Kirsten Kaya
Abstract: Purpose: To describe the development process of an existential support program and to explore participants' evaluation of supportive/unsupportive processes of change. Method: A five-day existential support program called "Energy for life" was designed including three main elements: 1. existential group counseling, 2. art therapy and 3. interaction with nature and aesthetic surroundings. The program was implemented at two different study sites. Focus group interviews were conducted to evaluate the program. Results: 40 subjects were recruited (20 for each one of the two study sites) and 36 completed the study (31 women, five men) in the age range from 31 to 76 years and living with cancer across all stages and types. The program resulted in supportive processes of "existential sharing". The existential group counseling included a sharing process which led to an increased awareness and acceptance of one's existential situation and a preparation for the next steps in one's life. Art therapy offered a respite from the illness or the opportunity to express and share difficult thoughts and feelings connected to the illness experience. The interaction with nature/surroundings induced feelings of calmness and peace, increasing self-worth and spiritual belonging. Unsupportive processes of change related to the organization of the existential counseling groups, feelings of discomfort with creative engagement and feelings of distress provoked by a hospital environment. Conclusion: Through "Energy for life" existential concerns and distress were shared, contained and transformed. Knowledge has been gained about how an existential support program can be designed that explicitly focuses on alleviating patients' existential distress. Highlights: Cancer causes existential concerns and problems that, if neglected, might lead to existential distress. Cancer patients can learn to better cope with existential distress by counseling and support. This study describes the development and evaluation of an existential support program called "Energy for life". "Existential sharing" is a vital component towards achieving renewed "energy for life" .